Individuación, ciencias humanas y humanismo en la teoría de G. Simondon (2017)
ABSTRACT: The process of psychic and collective individuation, proposed by Simondon, contributes to the debate on human sciences and humanism, as it considers the development of the being in its multiple phases. The concept of transindividual is chosen as a link between human sciences and humanism, in order to argue that in Simondon’s work come together an axiomatics (explanatory, scientific, rational power) and a humanist position (comprehensive, axiological) derived from the previous one. The following steps are developed in this article: 1) an axiomatics for human sciences: ontogenesis and individuation; 2) a transindividual dimension: between axiomatics and humanism; 3) a “renewed” humanism; and 4) a colophon on biopolitics and individuation.